POPULISM AND LOCAL DEMOCRACY: A WINNING ANALYSIS ON PAIR CANDIDATE OF CELLICA – JIMMY IN KARAWANG REGENT ELECTION 2015 - Maulana Rifai (THE INDONESIAN JOURNAL OF POLITICS AND POLICY (IJPP), 2019)
The major victory of the Cellica-Jimmy couples in the elections of the Karawang regency's head of 2015 with 51% of the vote to frustrate the other five candidates is an interesting phenomenon to be examined. The rise of populist politics has seeped into the local political scene by addressing the issues of local leader and immigrants as political campaigns. This study uses qualitative methods with a critical analysis that aims to describe the existing symptoms or reality. The findings in this study confirm that the populist issue and the campaign strategy of the Cellica-Jimmy couple gain the sympathy and support of voters in Karawang. So it is directly proportional to their victory. Keywords: populism, local democracy, karawang regent election 2015